"He imparted to me a sense of belonging. This is the greatest gift a person can receive" The academic learning experience of a sight impaired student - Lavian, Rivka Hillel (Advances in Social Sciences Research Journal, 2014)
In recent years, a growing number of students with special needs have been enrolled in higher education institutions. This increase has uncovered the need to introduce changes in the system in order to provide suitable support for these students. Understanding the academic, emotional and social difficulties they encounter and understanding their perception can help ease their inclusion and progress. This chapter presents the voice of a visually impaired special education teacher. Research has found that the desire to work in special education is closely related to a positive affair with personal or family misfortune (Hillel-Lavain. 2003, 2009; Tangala & Margaret, 2007). Avigail was accepted and studied during the years I served as Head of the Special Education Department. The autobiography she wrote describing her experiences as an academic student, has been holistically analyzed according to the four steps listed in the "Listening Guide" (Brown & Gilligan 1992, Gilligan et al 2003). The research question was: What is the learning experience of a visually impaired student studying in an academic setting? The findings show the voice of disability versus capabilities, with the clear message being the importance of including students with special needs in the academic world and offering them assistance and support both in the application process and throughout their studies.